2021
DOI: 10.1093/molbev/msab355
|View full text |Cite
|
Sign up to set email alerts
|

Endosperm Evolution by Duplicated and Neofunctionalized Type I MADS-Box Transcription Factors

Abstract: MADS-box transcription factors (TFs) are present in nearly all major eukaryotic groups. They are divided into Type I and Type II that differ in domain structure, functional roles, and rates of evolution. In flowering plants, major evolutionary innovations like flowers, ovules and fruits have been closely connected to Type II MADS-box TFs. The role of Type I MADS-box TFs in angiosperm evolution remains to be identified. Here, we show that the formation of angiosperm-specific Type I MADS-box clades of Mγ and Mγ-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 63 publications
3
23
0
Order By: Relevance
“…In a phylogenetic tree using two Capsella species as outgroups (C. rubella and C. grandiflora), the MADS-box genes were categorized into types and subgroups according to phylogenetic placement (Figure 2, Figures S8 and S9). As expected, the resulting tree separates type I from type II, as well as the three subgroups of type I (Ma, Mb, and Mc) and the two subgroups Gramzow & Theißen, 2013;Henschel et al, 2002;Parenicov a et al, 2003;Qiu & K€ ohler, 2022;Thangavel & Nayar, 2018). Monophyletic groups of Arabidopsis MADS-box genes, sharing a common ancestor with genes from the outgroup Capsella, are numbered starting from the top of the tree.…”
Section: Mads-box Gene Family Characterization Identifies Diagnostic ...supporting
confidence: 60%
See 2 more Smart Citations
“…In a phylogenetic tree using two Capsella species as outgroups (C. rubella and C. grandiflora), the MADS-box genes were categorized into types and subgroups according to phylogenetic placement (Figure 2, Figures S8 and S9). As expected, the resulting tree separates type I from type II, as well as the three subgroups of type I (Ma, Mb, and Mc) and the two subgroups Gramzow & Theißen, 2013;Henschel et al, 2002;Parenicov a et al, 2003;Qiu & K€ ohler, 2022;Thangavel & Nayar, 2018). Monophyletic groups of Arabidopsis MADS-box genes, sharing a common ancestor with genes from the outgroup Capsella, are numbered starting from the top of the tree.…”
Section: Mads-box Gene Family Characterization Identifies Diagnostic ...supporting
confidence: 60%
“…The Plant Journal, (2023), 116, 942-961 (Gramzow & Theissen, 2010;Parenicov a et al, 2003;Qiu & K€ ohler, 2022), the type I genes are primarily localized on chromosomes 1 and 5, hypothesized to be a result of recent and local duplications (Parenicov a et al, 2003). In A. lyrata and A. arenosa, however, we find that the MADSbox type I genes are distributed across all eight chromosomes (Figure 3).…”
Section: Variance In Mads-box Type I Gene Copy Numbermentioning
confidence: 72%
See 1 more Smart Citation
“…Specifically, the MADS domains in plants originated from the transformation of topoisomerase IIA subunit A ( TOPOIIA-A ) into MRCA and the latter’s subsequent modification to SRF-like and MEF2-like MADS-box genes. Furthermore, in angiosperms, type II MADS-box genes mediate major evolutionary innovations in plant flowers, ovules and fruits, whereas the formation of the M γ and interacting M α genes ( M α * ) of type I MADS-box can be traced back to the angiosperm ancestor and may be related to its heterodimeric function in angiosperm-specific embryonic trophoblast endosperm tissue ( Qiu and Claudia, 2021 ). This evolutionary process was affected by various events, including replication and functional differentiation, resulting in the functional diversity of their regulatory properties ( Ng and Yanofsky, 2001 ; Gramzow et al, 2010 ; Airoldi and Davies, 2012 ; Theissen et al, 2016 ; Schilling et al, 2020 ; Hsu et al, 2021 ; Tables 1 , 2 ; Figure 3 ).…”
Section: Evolution Of Gene Families In Plantsmentioning
confidence: 99%
“…Mδ and type I genes have been shown to participate in the A. thaliana male and female gametophytes. Recent studies suggested the role of type I MADS-box genes in the regulation of endosperm development in Arabidopsis and grasses [ 9 , 10 , 11 ]. Similarly, MIKC-type members of MADS-box have been widely studied for their ability to form transcription factor complexes and their vital role in the control of flowering development [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%